Religion and Conflict Attribution - Anthony, F. (Radboud Studies in Humanities, 2015)
Religion in a pluralistic society can play a dual role with regard to conflict. It can promote either violence or peace. Religion and Conflict Attribution examines the causes of interreligious conflict as perceived by Christian, Muslim and Hindu college students in Tamil Nadu, India.